INTENSITAS DAN PREVALENSI EKTOPARASIT PADA IKAN LELE DI BALAI BENIH IKAN LOKAL (BBIL) AIR MAWAR KOTA PANGKALPINANG - BUNGA SABILLA ALFIANIE PUTRI; ANGGUN LESTARI; MAYA MAYA; ANDRI KURNIAWAN (GANEC SWARA, 2023)
The research entitled "Intensity and Prevalence of Ectoparasites in Catfish at the Air Mawar Local Fish Seed Center (BBIL) Pangklapinang City" aims to determine the level of intensity, prevalence and types of ectoparasites that infect catfish in that location. Samples of 30 fish were taken randomly. In identifying ectoparasites, observations were made on the outside of the catfish's body, including mucus, fins and gills. Analysis of research data is descriptive and also presented in the form of pictures and tables. Data from the research results show that the types of ectoparasites that infect the external organs of the sampled fish include Dactylogyrus sp, Gyrodactylus sp, Argulus sp, Ichhtyobodo sp, Trichodina sp, and Cichlidogyrus sp. The prevalence rate of parasites that infect catfish is 90% with the category almost always and severe infection. The highest intensity of ectoparasites that attack catfish is by the parasite Dactylogyrus sp with an intensity value of 6.48 individuals per fish in the medium category, and the lowest intensity value is by the parasite Trichodina sp with an intensity value of 1 individual per fish. It is also known that the water conditions in the catfish pond This is not good for the survival of catfish, because the oxygen levels are low and the ammonia levels are high